Canine separation anxiety: strategies for treatment and management - Sargisson RJ (Dove Medical Press, 2014)
Rebecca J Sargisson School of Psychology, University of Waikato, Tauranga, New ZealandAbstract: Dogs with separation-related behavior problems engage in unwanted behavior such as destruction of property and excessive vocalization when left alone, causing distress for both the dog and the owner, and often leading to the dog being relinquished or euthanized. I review research on factors likely to predispose dogs to developing separation anxiety and on the treatments available. Although research is equivocal, dogs seem to develop separation-related behavior problems if they are male, sourced from shelters or found, and separated from the litter before they are 60 days old. Protective factors include ensuring a wide range of experiences outside the home and with other people between the ages of 5–10 months, stable household routines and absences from the dog, and the avoidance of punishment. The most successful treatment for canine separation-related problems may be behavior modification that focuses on systematic desensitization and counterconditioning, which can be supplemented with medication in the initial stages. Where individual therapy from an animal behavior expert is not possible, advice to dog owners should be clear, simple, and contain five or fewer instructions to improve adherence. Advice is given for people seeking to adopt a dog, for new dog owners, and for existing dog owners who wish to treat their dog’s separation anxiety.Keywords: systematic desensitization, counterconditioning, medication, separation anxiety